Elementos y obstáculos a tomar en cuenta en la conceptuación y apropiación de los derechos sexuales y reproductivos - Ortiz-Ortega, Adriana (El Colegio de México A.C., 2004)
The article places the concept of sexual rights within the sphere of the social sciences. It shows the role of various actors and social processes in the evolution of a concept that it is still struggling to gain social legitimacy. It shows how sexual rights belong to the sphere of ethics, law and the exercise of citizenship as opposed to the view of orthodox religions, which consider that sexuality belongs to the sphere of nature rather than law. The author contrasts the religious position with the role of social movements and the United Nations Conference in facilitating the construction of discourse. Finally, the article ends by offering an evaluation of the appropriation of sexual rights by women in contemporary Mexico.